APPLICATION OF AUGMENTED REALITY TECHNOLOGY AS A LEARNING MEDIA - Ali, Muhammad Mahrus (Universitas Teknokrat Indonesia, 2024)
Augmented Reality (AR) is a concept of combining virtual reality with world reality. The benefits of technology at this time have greatly influenced human life, with the creation of sophisticated machines or tools that humans use to achieve human needs. Augmented Reality is an environment that incorporates virtual 3D objects into a real environment. Augmented Reality is growing very rapidly so that it supports the development of this application in various fields including learning media. Elementary school students find it difficult to understand the material of geometry, because without teaching aids students are only able to imagine or imagine the object of the geometry. Because this requires a learning application for geometry by applying Android-based Augmented Reality technology that can display 3d space shapes along with elements and formulas that apply to the material. Seeing these objectives, the researcher took the type of Research and Development Method or what in English is called R&D (Research and Development), which is a method used to produce a certain product and test the effectiveness of the product (Sugiyono, 2009: 297). The calculation method uses the one-way ANOVA method. The trial was carried out at SD Islam Pasuruan. It was tested on students in grades VI A and B and 18 participants were taken randomly and divided into 3 groups consisting of 6 students in each group. The results obtained from the calculation analysis using one-way Anova with F_count = 4.68 greater than F table = 3.68 with a significant level of 5% (0.05). Furthermore, the Scheffe test was performed to compare the values between groups. With the results, the first group (5.30) has a greater value than the second (2.65) and third (2.652) groups. This application can be installed and running on all types of android used in testing, and the recommended best distance between mobile devices to detect markers is 40 cm - 90 cm for all marker sizes, namely 10 cm, 15 cm and 20 cm in size.